2019
DOI: 10.7554/elife.40226
|View full text |Cite
|
Sign up to set email alerts
|

Human pancreatic cancer cell exosomes, but not human normal cell exosomes, act as an initiator in cell transformation

Abstract: Cancer evolves through a multistep process that occurs by the temporal accumulation of genetic mutations. Tumor-derived exosomes are emerging contributors to tumorigenesis. To understand how exosomes might contribute to cell transformation, we utilized the classic two-step NIH/3T3 cell transformation assay and observed that exosomes isolated from pancreatic cancer cells, but not normal human cells, can initiate malignant cell transformation and these transformed cells formed tumors in vivo. However, cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 50 publications
1
53
0
Order By: Relevance
“…It has been reported that some chemotherapies induce CAFs to start to release more exosomes, which in turn promote pancreatic cancer cell proliferation and drug resistance [89]. Exosomes also play a role as cell transformation initiator in human pancreatic cancer; a recent study reported that pancreatic cancer cell exosomes were involved in malignant cell transformation of NIH/ 3 T3 cells, contrarily, this was impossible on exosomes from healthy pancreatic cells or primary fibroblast cells [90]. Macrophages-delivered exosomes are one of the pancreatic cancers TME components, and they are said to be involved in different PC essential events.…”
Section: Mir-550mentioning
confidence: 99%
“…It has been reported that some chemotherapies induce CAFs to start to release more exosomes, which in turn promote pancreatic cancer cell proliferation and drug resistance [89]. Exosomes also play a role as cell transformation initiator in human pancreatic cancer; a recent study reported that pancreatic cancer cell exosomes were involved in malignant cell transformation of NIH/ 3 T3 cells, contrarily, this was impossible on exosomes from healthy pancreatic cells or primary fibroblast cells [90]. Macrophages-delivered exosomes are one of the pancreatic cancers TME components, and they are said to be involved in different PC essential events.…”
Section: Mir-550mentioning
confidence: 99%
“…Exosome is a member of EV, with the size of 40-150 nm. It packages the proteins and genetic materials from host cells into lipid bilayer and delivers this cargo to the recipient cells 12,13 . This communicational approach can increase the spreading scope and duration time of the signals.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer (PAC) is a devastating metastatic disease that severely threatens the human health [28]. Epidemiological investigation identified that the incidence and mortality of PAC raised year by year all over the world [29,30].…”
Section: Discussionmentioning
confidence: 99%